Feet first (rotatable shoe rack) / Sarah Najwa Junaidey ...[et al.] - Junaidey, Sarah Najwa; Noor Azmee, Sara Nur Imani; Saiful Muzamir, Sarah Qistina; Herman, Siti Humaira; Mohd Shazniff, Nursyasya Humaira
Shoe racks, with several different designs, are common furniture storage units available in the current market. Ergonomic researchers and designers have created new ergonomic shoe racks due to usability problems in existing conventional shoe rack designs that can lead to users experiencing certain kinds of musculoskeletal injuries or discomforts. In these existing ergonomic shoe racks, however, there are several weaknesses that can prevent usability. Feet First an attempt to design and create a rotatable shoe rack that implements solutions to the flaws in the current ergonomics for enhanced usability. Two hand-drawn model design phases with selection matrices were developed after performing market analysis and listing the pros and cons of available shoe rack designs on the market to choose the most possible design prototype to be used. The design process of the selected prototype rotatable shoe rack was first conducted using Solidworks software. Overall, the rotatable shoe rack Feet First can be considered as a good functional product according to the performance, data and feedback collected from the testing as it manages to achieve all of the objective.